2007
DOI: 10.1089/ten.2006.0315
|View full text |Cite
|
Sign up to set email alerts
|

Expanded Adipose-Derived Stem Cells Suppress Mixed Lymphocyte Reaction by Secretion of Prostaglandin E2

Abstract: Multipotent mesenchymal stem cells (MSCs) in adult tissue are known to be less immunogenic and immunosuppressive. Previous study showed that primary cultures of human adipose-derived stem cells (ADSCs) shared their immunomodulatory properties with other MSCs. However, whether passaged human ADSCs can retain their immunomodulatory effect after in vitro expansion remains unknown. In addition, the mechanism of ADSC-mediated immunomodulatory effect remains to be elucidated. This study aimed to investigate these is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
198
2
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 250 publications
(213 citation statements)
references
References 39 publications
10
198
2
3
Order By: Relevance
“…Similar to BM-MSCs (23,(40)(41)(42), PGE 2 and IL-10 seem to play a critical role in the suppressive effect of human AD-MSCs. Importantly, human AD-MSCs express various Toll-like receptors and become activated in response to different inflammatory mediators and bacterial products (43).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similar to BM-MSCs (23,(40)(41)(42), PGE 2 and IL-10 seem to play a critical role in the suppressive effect of human AD-MSCs. Importantly, human AD-MSCs express various Toll-like receptors and become activated in response to different inflammatory mediators and bacterial products (43).…”
Section: Discussionmentioning
confidence: 94%
“…Human MSCs obtained from subcutaneous adipose tissue (AD-MSCs) have recently emerged as an attractive alternative source of MSCs for cell therapy (7,8,10,21). Large amounts of human AD-MSCs can be easily obtained from lipoaspirates from healthy donors and rapidly expanded in vitro to generate a clinically effective dosage, and recent studies have reported that human AD-MSCs share some of the immunomodulatory properties that characterize the BM-MSCs (18,22,23). Importantly, we recently found that human AD-MSCs exert profound suppressive responses on collagen-reactive T cells from RA patients through various ways (24).…”
mentioning
confidence: 99%
“…As such, it was concluded that allogeneic transplantation of BMSC and ADSC could be employed for tissue engineering [37]. In another study the lack of MHC-II expression in ADSCs was corroborated [31].…”
Section: Evidence For Adsc's Immunomodulatory Capacity: Cell Culturementioning
confidence: 89%
“…Moreover, the immunosuppressive effect appeared to require cell-cell contact. However, in 2 separate studies the cell-cell contact requirement was corroborated [30] and disputed [31], respectively. Regardless of this disagreement, the immunosuppressive effect of ADSC has been consistently observed in all subsequent relevant studies [32][33][34][35][36].…”
Section: Evidence For Adsc's Immunomodulatory Capacity: Cell Culturementioning
confidence: 97%
“…MSCs secrete soluble mediators and directly interact with T-cells to modulate their activity [29,36,37]. MSCs can induce apoptosis of activated T cells, induce cell cycle arrest, decrease T-cell proliferation [30,38] and alter T cell phenotype. MSCs target T-cell subsets (CD4+, CD8+, CD2+ and CD3+ subpopulations) equally [30].…”
Section: T Lymphocytesmentioning
confidence: 99%